Why isn't the function Y̅=C(Y̅–T̅)+I(r)+G̅, actually: Y̅=C(Y̅–T̅)-S+I(r)+G̅, or Y̅=C(Y̅–T̅)+G̅ ?
What is my reasoning behind this:
The consumption function includes all the money you are legally allowed to spend (ie: after paying taxes). But, as we know, a part of this money can be saved.
We know that:
The consumption function is the amount of money one can choose to either consume or save. So, why not removing the Savings option?
The function Y̅=C(Y̅–T̅)+I(r)+G̅ can be altered to: Supply of Y= Demand of Y. And I don't think that savings are part of the Demand of Y. That is why, we would have to deduct it from the equation?
So, do we write: Y̅=C(Y̅–T̅)+I(r)+G̅, instead of Y̅=C(Y̅–T̅)-S+I(r)+G̅, because S<I(r)? How could we even compare savings to the interest "RATES"?
Where am I wrong?